Tinjauan Proses Pengisian Persetujuan Tindakan Kedokteran Di Ruang Bedah RSUD H. Damanhuri Barabai Tahun 2014 - Deasy Rosmala Dewi; Ani Kipatul Hidayah; Anisa Batunnajariah; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2015)
Research the process of filling the medical action approval in Yakud Room (Surgical Room) RSUD H. Damanhuri Barabai has been done, but 14 medical record were analyzed in March, 9 of them incomplete documentation on the part of the explanation. The purpose of the study is to describe the filling process of medical action approval in Yakud Room (Surgical Room) RSUD H. Damanhuri Barabai. This research uses descriptive method. Sample in this research is the filling process of the medical action approval and the provision of information in Yakud Room (Surgical Room) RSUD H. Damanhuri Barabai period 12 May 2014 to 24 May 2014 amounted 7 process . The result of this study are medical action approval in Yakud Room (Surgical Room) RSUD H. Damanhuri Barabai using 2 different forms. The first form used medical form of informed consent to inpatient consent while the second form used for explanation and consent documentation of patients requiring medical on surgical measures. Approval or consent was given after the patient or family received explanation for the measures. Parties are allowed to fill out informed consent is patient, the wife or husband, children, parents, and other relative of patients. Patient’s rights in informed consent fill out is the right to receive an expalantion, the right to approve and reject the recommended medicalaction, and the right to discuss the disease and the patient required actions. Obligations patient in fill out informed consent is listening to an explanation of the disease and the patient required actions. Signed a letter of approval or denial of surgical measures and believe in the ability of physicians.